The Importance of Optimization in the Process of Education - Ziyatovich, Davronov Pirnazar; Pirnazarovna, Davronova Fotima (Miasto Przyszłości, 2024)
The method of achieving optimality in teaching based on the "Problem-based educational methodology" is described in the article.